2002
DOI: 10.1002/1521-4176(200207)53:7<471::aid-maco471>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion of alumina/titanium diboride composites in neutral and acidic chloride solutions

Abstract: This research concerns the study of the corrosion behaviour of monolithic titanium diboride and the composites 50%Al2O3/50%TiB2 (50/50) and 70%Al2O3/30%TiB2 (70/30) in 3.5% NaCl solutions, at pH 7 and 3 (adjusted by HCl additions). The test temperature is 45 ± 1°C. Both electrochemical and chemical techniques are applied. Scanning electron microscope (SEM) observations are also used to investigate the corrosion attack morphology. Polarization curve recording evidences that at short immersion times both composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…4a) indicates a feature of Warburg impedance. This effect can be attributed to a diffusion control of ions from the electrode to the bulk solution [15]. Bode plots in Fig.…”
Section: Electrochemical Impedance Spectroscopymentioning
confidence: 96%
See 2 more Smart Citations
“…4a) indicates a feature of Warburg impedance. This effect can be attributed to a diffusion control of ions from the electrode to the bulk solution [15]. Bode plots in Fig.…”
Section: Electrochemical Impedance Spectroscopymentioning
confidence: 96%
“…The corrosion resistance mainly depends on the general coating integrity and quality based on the aspects such as but not limited to adhesion, porosity, roughness, coating passive film, kinetics of the passive film formation and its resistance. When titanium diboride is immersed in NaCl solution at room temperature, it behaves like a passive metal due to the formation of a surface oxide film (hydrated titanium dioxide), whose protectivity decreases with the temperature and completely vanishes at 65 °C [15], [38]. In salt rich ocean water, a white film of tetravalent oxide titanium TiO2-H2O is formed, which hinders the material dissolution [13], [38].…”
Section: Microstructural Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The electrodes were prepared according to the procedures described elsewhere [19], with a surface area of 1 cm 2 . After polishing down to 1 m by diamond paste, degreasing by acetone and drying, they were exposed to the following aqueous solutions at 45 ± 1 • C, under natural aeration conditions: For the electrochemical experiments a three-electrode cell was used, equipped with a Pt auxiliary electrode and a saturated calomel reference electrode (SCE).…”
Section: Corrosion Tests and Characterization Methodologiesmentioning
confidence: 99%
“…The addition is expected to enhance the mechanical properties as well as the corrosion resistance of the composites. There are research works that have shown that titanium-diboride behaves like a passive metal in acid and salt environments, due to the formation of a surface oxide film, whose protective power, decreases with temperature [16,17].…”
Section: Introductionmentioning
confidence: 99%